Urine Cotinine Screening Detects Nearly Ubiquitous Tobacco Smoke Exposure in Urban Adolescents. Issue 9 (28th December 2016) - Benowitz, Neal L; Jain, Shonul; Dempsey, Delia A; Nardone, Natalie; Helen, Gideon St.; Jacob, Peyton
Abstract: Introduction: Routine biochemical assessment of tobacco smoke exposure could lead to more effective interventions to reduce or prevent secondhand smoke (SHS)-related disease in adolescents. Our aim was to determine using urine cotinine (major nicotine metabolite) measurement the prevalence of tobacco smoke exposure among adolescents receiving outpatient care at an urban public hospital. Methods: Surplus urine was collected in 466 adolescents attending pediatric or urgent care clinics at Zuckerberg San Francisco General Hospital, serving families with lower levels of income and education, in 2013–2014. The majority were Hispanic or African American. Urine cotinine cut points of 0.05 to 0.25 ng/ml, 0.25 to 30 ng/ml, and 30 ng/ml were used to classify subjects as light SHS or thirdhand smoke exposed, SHS or light/intermittent active users, and active tobacco users, respectively. Results: Among subjects 87% were exposed, including 12% active smoking, 46% SHS and 30% lightly exposed. The SHS exposed group adjusted geometric mean cotinine values were significantly higher in African Americans (1.48 ng/ml) compared to other groups (0.56–1.13 ng/ml). Conclusions: In a city with a low smoking prevalence (12%), a large majority (87%) of adolescents seen in a public hospital clinic are exposed to tobacco. This is much higher than reported in national epidemiological studies of adolescents, which used a plasma biomarker. Since SHS is associated with significant respiratory diseases and parents and adolescents underreport exposure to SHS, routine biochemical screening should be considered as a tool to reduce SHS exposure. The clinical significance of light exposure needs to be investigated. Implications: Urine biomarker screening found that a large majority (87%) of adolescents treated in an urban public hospital are exposed to tobacco. Since SHS is associated with significant respiratory diseases and parents and adolescents underreport exposure to SHS, routine biochemical screening should be considered as a tool to reduce SHS exposure.